Phase II study of adjuvant chemotherapy with pemetrexed and cisplatin with a short hydration method for completely resected nonsquamous non‐small cell lung cancer. Issue 9 (30th July 2020) - Tachihara, Motoko; Dokuni, Ryota; Okuno, Keiko; Tokunaga, Shuntaro; Nakata, Kyosuke; Katsurada, Naoko; Yamamoto, Masatsugu; Nagano, Tatsuya; Kobayashi, Kazuyuki; Tanaka, Yugo; Funada, Yasuhiro; Maniwa, Yoshimasa; et al.
Abstract : Background: Cisplatin (CDDP) and vinorelbine as an adjuvant chemotherapy improve the overall survival of patients with completely resected non‐small cell lung cancer (NSCLC). However, the treatment completion rate is low due to severe adverse events (AEs). Pemetrexed (PEM) has been used in advanced NSCLC due to its high safety and efficacy. Additionally, the safety of a short hydration method for CDDP administration has been previously reported. Here, we investigated the feasibility of CDDP plus PEM with a short hydration method as adjuvant chemotherapy. Methods: A total of 21 completely resected nonsquamous NSCLC patients with pathological stage IIA to IIIA disease were enrolled into the study. Adjuvant chemotherapy consisted of four cycles of CDDP (75 mg/m 2 ) plus PEM (500 mg/m 2 ) every three weeks with a short hydration method. The primary endpoint was the treatment completion rate, and the secondary endpoints included toxicity, the two‐year relapse‐free survival (RFS) rate, and the outpatient treatment rate. Results: A total of 21 patients (median age: 66 years; 12 males) were enrolled in two centers. All cases were adenocarcinoma with PS0 (71.4%) or PS1 (28.6%). A total of 81.0% of the patients received four cycles of therapy as scheduled and the primary endpoint was met. The rate of outpatient chemotherapy completion after the second cycle was 90.5%. The grade 3 or higher toxicities were anorexia ( n = 2) and pulmonary thromboembolism ( n = 1). No grade 3/4 hematological toxicities or creatinine level elevations were observed. The two‐year RFS rate was 57.3%. Conclusions: CDDP and PEM with a short hydration is well tolerated in the outpatient setting with limited toxicity. Key points: Significant findings of the study: CDDP plus PEM adjuvant therapy with a short hydration method is well tolerated in the outpatient setting with limited toxicity. What this study adds: CDDP plus PEM with a short hydration method has the potential to be one of the options of adjuvant therapy in the future. Abstract : CDDP plus PEM adjuvant therapy with a short hydration method is well tolerated in the outpatient setting with limited toxicity.